DETERMINANTS OF FIRM VALUE IN INDONESIAN ENERGY FIRMS: THE ROLE OF ECO-EFFICIENCY, GREEN INNOVATION, CARBON EMISSION DISCLOSURE, AND GREEN ACCOUNTING - Nur Mala; Indra Gunawan Sireigar (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study analyzes the effect of eco-efficiency, green innovation, carbon emission disclosure, and green accounting on firm value in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. Using a quantitative approach with an associative hypothesis design, 15 companies were selected through purposive sampling, yielding 75 firm-year observations. Panel data regression with EViews 12 was employed, and the Random Effect Model (REM) was selected based on Chow, Hausman, and Lagrange Multiplier tests. The results show that eco-efficiency has no significant effect on firm value (p = 0.6972), while green innovation (p = 0.0024) and carbon emission disclosure (p = 0.0085) have positive and significant effects. Green accounting shows no significant effect (p = 0.2773). These findings indicate that environmental innovation and transparency are more valued by the market than environmental efficiency or green accounting implementation in enhancing firm value. The study is limited to energy sector companies on the IDX, and the 2020–2024 observation period is relatively short. Future research should expand to other sectors, extend the timeframe, and include variables such as environmental performance ratings, corporate governance, or regulatory factors. Energy companies should prioritize green innovation and carbon disclosure to improve firm value and attract environmentally conscious investors. Policymakers should incentivize green innovation and standardized carbon disclosure practices. This study contributes empirical evidence on the differential effects of these environmental practices on firm value in the Indonesian energy sector context.